Proteolysis at the Archaeal Membrane: Advances on the Biological Function and Natural Targets of Membrane-Localized Proteases in Haloferax volcanii - De Castro, Rosana E.; Giménez, María I.; Cerletti, Micaela; Paggi, Roberto A.; Costa, Mariana I. (Frontiers in Microbiology, 2022)
Proteolysis plays a fundamental role in many processes that occur within the cellular membrane including protein quality control, protein export, cell signaling, biogenesis of the cell envelope among others. Archaea are a distinct and physiologically diverse group of prokaryotes found in all kinds of habitats, from the human and plant microbiomes to those with extreme salt concentration, pH and/or temperatures. Thus, these organisms provide an excellent opportunity to extend our current understanding on the biological functions that proteases exert in cell physiology including the adaptation to hostile environments. This revision describes the advances that were made on archaeal membrane proteases with regard to their biological function and potential natural targets focusing on the model haloarchaeon Haloferax volcanii.